PENERAPAN STRATEGI RELATING, EXSPERIENCING, APPLYING, COOPERATING AND TRANSFERING (REACT) TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VIII - Beni Junedi; Dona Marta Ayu (MES: Journal of Mathematics Education and Science, 2018)
Abstract. The purpouse of this study is to know the understanding of the mathematical concepts of students with the application of REACT learning strategies better than the understanding of mathematical concepts of convensional learning students. This type of research is Quasi Exsperiment with Randomized Subjects Posttest Only Control Group Design. Population of students of class VIII SMP Negeri 3 Pasir Penyu. Sampling is done by Random Sampling. The classes selected to be the experimental class are class VIII4 and the control class is class VIII3. Data collection techniques used test instrument understanding students’ math concepts. The technique of data analysis using t-test as hypothesis test, with pre- requirement test is normality test and homogeneity test. Based on the calculation of the dip- t test taritmethic =2,113 and ???????????????????????? =2,005, because ????????????????????????????????ℎ???????????????????????????????? so it can be concluded that ???????? accepted means the hypothesis proposed in accepted researcth that is the understanding of mathematical concepts by applying REACT’s strategy of learning is better than the understanding of mathematical concepts of students using convensional learning class VIII SMP Negeri 3 Pasir Penyu.Keywords: Relating, Exsperiencing, Applying, Cooperating and Transfering (REACT), understanding concepts.